Finite element analysis on drawing of copper wire containing an inclusion and a cavity - Somchai Norasethasopon; Kazunari Yoshida (2003)
In this paper the influence of an eccentric inclusion and cavity on copper shaped-wire drawing were investigated. An experimental investigation for optimal die half-angle was conducted. Based on experimental data of optimal die half-angle, the deformations, the mean normal stress and the plastic strain of both copper shapedwires containing an eccentric inclusion and cavity were calculated by finite element analysis. The same parameters for both copper shaped-wires containing a centric inclusion and cavity were also calculated using the same method. Necking, bending and misalignment were observed during drawing of a wire containing an eccentric inclusion. However only necking was observed during drawing of a wire containing a centric inclusion. It was found that the inclusion rotated during drawing and extremely compressive stress occurred on the die contact surface during drawing of wire containing eccentric inclusion. For the same inclusion size, the drawing stress was strongly .influenced by inclusion size and slightly influenced by eccentric length. The drawing stress of wire containing centric inclusion was greater than that of wire containing eccentric inclusion. It was found that the drawing stress decrement was due to- a cavity and the deformation behaviour of a wire containing a cavity was opposite to that of a wire containing an inclusion